Description of Mother's Knowledge and Attitude about the Motor Development of Toddlers in Bandar District - Ricard Fredrik Marpaung (Science Midwifery, 2022)
Given the role of the mother in the development of toddlers, it is necessary to know the mother's knowledge about child development. Knowledge about child development can be obtained through education, self-experience and the experience of others, mass media and the environment. When compared with Western countries, the motor development of Indonesian children is relatively low. This type of research is descriptive which aims to determine the knowledge and attitudes of mothers who have toddlers about motor development in toddlers in Bandar District, Simalungun Regency. In this study, the sample was taken using a total sampling technique, namely the entire population was sampled as many as 30 people. Based on the research results, the majority of respondents aged 20-24 years were 13 people (43.3%), minority aged 25-29 years were 8 people (26.7%). The majority of high school education is 14 people (46.7%), the minority is elementary school education 4 people (13.3%). The majority of work as housewives are 8 people (26.7%), the minority are employees of BUMN as many as 4 people (13.3%). The majority of knowledge lacked 16 people (53.3%), the minority had good knowledge as many as 14 people (46.7%). The majority of the attitude agreed that as many as 10 people (33.3%), the minority had a disapproval attitude that was as many as 5 people (16.7%). Puskesmas must provide information related to motor development in toddlers either through posyandu or other activities that involve mothers.